Relation between the electroforming voltage in alkali halide-polymer diodes and the bandgap of the alkali halide - Bory, B. F. (2015)
Electroforming of indium-tin-oxide/alkali halide/poly(spirofluorene)/Ba/Al diodes has been investigated by bias dependent reflectivity measurements. The threshold voltages for electrocoloration and electroforming are independent of layer thickness and correlate with the bandgap of the alkali halide. We argue that the origin is voltage induced defect formation. Frenkel defect pairs are formed by electron-hole recombination in the alkali halide. This self-accelerating process mitigates injection barriers. The dynamic junction formation is compared to that of a light emitting electrochemical cell. A critical defect density for electroforming is 10(25)/m(3). The electroformed alkali halide layer can be considered as a highly doped semiconductor with metallic transport characteristics. (C) 2014 Author(s).